2016 IEEE/ACS 13th International Conference of Computer Systems and Applications (AICCSA) 2016
DOI: 10.1109/aiccsa.2016.7945693
|View full text |Cite
|
Sign up to set email alerts
|

A classification methodology for security patterns to help fix software weaknesses

Abstract: Security patterns are generic solutions that can be applied since early stages of software life to overcome recurrent security weaknesses. Their generic nature and growing number make their choice difficult, even for experts in system design. To help them on the pattern choice, this paper proposes a semiautomatic methodology of classification and the classification itself, which exposes relationships among software weaknesses, security principles and security patterns. It expresses which patterns remove a give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…After having studied the CAPEC base, we observed that attacks are described with a set of CWE weaknesses, a set of security principles and potential solutions and mitigations. These security activities can also be found in our previous classification (Regainia et al, 2016a), connecting weaknesses with security patterns. However, we noticed that the mitigations and security principles available in the attack documents often have a high level of abstraction making their use difficult.…”
Section: Classification Methodologymentioning
confidence: 82%
See 4 more Smart Citations
“…After having studied the CAPEC base, we observed that attacks are described with a set of CWE weaknesses, a set of security principles and potential solutions and mitigations. These security activities can also be found in our previous classification (Regainia et al, 2016a), connecting weaknesses with security patterns. However, we noticed that the mitigations and security principles available in the attack documents often have a high level of abstraction making their use difficult.…”
Section: Classification Methodologymentioning
confidence: 82%
“…In Step 2, we collect the relationships between every attack and CWE weaknesses, reflecting which weakness is targeted by an attack. In Step 3, we reuse our earlier classification (Regainia et al, 2016a) to extract for every CWE weakness, the security principles, mitigations and security patterns which fix the weakness. After the consolidation of the different databases built in the previous steps, we obtain a database DB f from which the classification is automatically extracted in Step 4.…”
Section: Classification Methodologymentioning
confidence: 99%
See 3 more Smart Citations